Three-dimensional hierarchical self-supported multi-walled carbon nanotubes/tin(IV) disulfide nanosheets heterostructure electrodes for high power Li ion batteries - Kang, Jin-Gu; Lee, Gwang-Hee; Park, Kyung-Soo; Kim, Sang-Ok; Lee, Sungjun; Kim, Dong-Wan; Park, Jae-Gwan (Royal Society of Chemistry, 2012)
It is of great significance to improve the power density of Li ion batteries (LIBs) in pursuit of high-end products and technologies. Herein, we investigated the three-dimensional (3D) hierarchical self-supported multi-walled carbon nanotubes (MWCNTs)/tin(IV) disulfide nanosheets (SnS2 NS) heterostructured electrodes, demonstrating superior rate capabilities of 480 and 420 mAh g(-1) even at the very high c-rates of 5C and 10C (charging in 6 min), respectively. The origins of the enhancement of the rate capabilities were discussed in detail by focusing on the roles of MWCNTs, which were directly grown on the metallic current collector. Furthermore, we have delicately dealt with the in-plane and plane-normal growth mechanisms of hexagonal SnS2 NS from the crystallographic point of view.